Hurdles for Starting Ministernotomy Aortic Valve Replacement Program - Suraj Wasudeo Nagre (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
In this era of percutaneous interventions and minimal invasive surgery, ministernotomy aortic valve replacement is good option to start minimal invasive cardiac surgery in any institute. Aortic valve replacement seems more feasible through ministernotomy as aorta is anterior structure and cannulation required can be done through exposed aorta and right atrium [1]. Most importantly it can be done with same intruments that are used in conventional full sternotomy aortic valve replacement. Patients with same criteria (Table 1), are selected and divided into two groups. In Group one 10 cases undergone ministernotomy AVR anvd in Group two 10 cases undergone conventional full sternotomy AVR. Observations in both groups are compared.